Construction of healthy and palatable diet for low socioeconomic female adults using linear programming - Rajikan R.; Zaidi N.I.A.; Elias S.M.; Shahar S.; Manaf Z.A.; Yusoff N.A.M. (Insight Society, 2024)
Indexed by SCOPUS